Efectos hemodinámicos de la anestesia intravenosa total Tiva frente a la anestesia general baanceada en el Hospital de Clínica Pichincha y el Hospital Manuel Ygnacio Monteros de la ciudad de Loja durante el año 2013. - Silva Romero, Doris (2013)
Anesthesia is a procedure by which certain drugs administered to the patient producing a state of reversible unconsciousness with the ability to override certain reflexes and maintaining adequate autonomy. Hemodynamics is known as the scientific field that studies the relationships between the physical principles that govern the pressure, flow and resistance complianza applied to the cardiovascular system. Objective: To evaluate the hemodynamic effects (blood pressure, mean arterial pressure and heart rate) for a laparoscopic surgical procedure between total intravenous anesthesia and General anesthesia Balanced. The study was performed with a clinical design, comparative and descriptive controlled which included 60 patients between the ages of 18 to 60 years, ASA I - II, undergoing laparoscopic surgery in the operating room of the Hospital de Clinics Pichincha and Hospital Manuel Ygnacio Monteros city of Loja. The groups were distributed equally ie 30 patients for each anesthetic technique. In both groups, hemodynamic variables were recorded during induction, after laryngoscopy during anesthetic maintenance at the end of the surgery, waking and the patient extubated . The Student t test was applied, it was observed that the total intravenous anesthesia in the induction times (p = 0.217) and at the time of intubation p = 4 0.684 is greater than 0.05 ( P > 0.05 ) there is no statistically significant difference between the mean value of the initial FC and the values at the time of induction, intubation and anesthetic maintenance . In balanced general anesthesia induction times (p = 0.260 ) and in the moment of intubation p = 0.423 is greater than 0.05 ( P > 0.05), there are no statistically significant differences between the mean value initial FC and the values at the time of induction, intubation and anesthetic maintenance . This means that the total intravenous anesthesia, as feature balanced general anesthesia in hemodynamically stable condition heart rate at the time of induction and intubation. Keywords: general balanced anesthesia, total intravenous anesthesia, hemodynamic. .